Citizenship Development Model in Democracy According to Buddhist Guidelines of People in Nonthaburi Province - Chatchorpha, Abhinya (Journal of MCU Social Science Review, 2023)
Objectives of this research were to study citizenship character in a democratic system of people in Nonthaburi Province, to study the component of citizenship development in a democratic system of people in Nonthaburi Province, and to propose the model of citizenship development in a democratic system according to Buddhist guideline of people in Nonthaburi Province, conducted by the qualitative research method, in-depth-interviewing 25 key informants using a structured in-depth-interview script, analyzed data by content descriptive interpretation by analytic induction bringing data from interviews to be systematically organized and classified. Findings were as follows: 1. Citizenship characteristics in a democratic system of people in Nonthaburi Province consisted of: 1) self and social responsibility, 2) respecting the equality principle and other’s rights, 3) respecting individual differences, and 4) respecting rules and regulations. 2. The components of citizenship development in a democratic system of the people in Nonthaburi Province consisted of; 1) power by knowledge, 2) operational power, and 3) opinion power and attitude. 3. A model of citizenship development in a democratic system according to Buddhism of the people in Nonthaburi Province according to Sappurisadhamma 7 consisted of 1) Dhammanyuta, 2) Atthanyuta, 3) Attanyuta, 4) Mattanyuta, 5) Kalanyuta, 6) Parisanyuta, and 7) Puggalanyuta.